On forward-adaptive versus forward/backward-adaptive SISO algorithms for Rayleigh fading channels - Hansson, A.; Chugg, K.M.; Aulin, T. (IEEE communications letters, 2001)
Two types of soft-input soft-output (SISO) algorithms have previously been proposed for iterative decoding of concatenated codes applied over fading channels; forward-adaptive algorithms exploit the dependency between the present symbol interval and past symbol intervals, while forward/backward-adaptive algorithms take both the past and the future into account. Numerical results presented for interleaved serially concatenated continuous phase modulation (CPM) over the Rayleigh fading channel indicate that the performance of forward-adaptive algorithms approaches the performance of forward/backward-adaptive algorithms when a long channel-memory depth is exploited.